Hydraulic Conductivity - Rodrigues da Silva, Vanderlei (IntechOpen, 2013)
This book is a research publication that covers original research on developments within the Hydraulic Conductivity field of study. The book is a collection of reviewed scholarly contributions written by different authors. Each scholarly contribution represents a chapter and each chapter is complete in itself but related to the major topics and objectives.